Low TEMPERATURE AuTOCATALYTIC NICKEL DEPOSITION (Biological Sciences - PJSIR, 2003)
Autocatalytic nickel deposition was first patented in 1955. This work was carried out to develop an autocatalytic nickel deposition process at lower temperatures. This process was based on same electrolytes and reducing agents viz; hypophosphite but it worked at lower temperature and contained sodium fluoride. Plating rate was good and the depo sits contained less phosphorous content. It was also observed that the deposits have good adhesion and was comparable with electrodeposited nickel in corrosion resistance and relatively easy in the practical application of   deposition.